MPERFORATE HYMEN AND SUBSEQUENT MUCOVAGINA IN A FILLY - PANDEY, R R; KUMAR2, B; SCHAN, V; SAXENA, A; YADAV, D (The Indian Journal of Animal Reproduction, 2022)
An eighteen-month-old filly was presented with imperforate hymen and subsequent development of mucovagina. The hymen was incised and accumulated secretion was drained. The linear incision of hymenal membrane was bluntly extended through digital manipulation till smooth passage of hand in vaginal canal without any resistance and cervix was palpated. Animal recovered uneventfully, bred after seven months and diagnosed positive for pregnancy at three months of gestation.